Using Remote Sensing Methods to Study Active Geomorphologic Processes on Cantabrian Coastal Cliffs - María José Domínguez-Cuesta; Laura Rodríguez-Rodríguez; Carlos López-Fernández; Luis Pando; José Cuervas-Mons; Javier Olona; Pelayo González-Pumariega; Jaime Serrano; Pablo Valenzuela; Montserrat Jiménez-Sánchez (Remote Sensing, 2022)
Gravitational processes on inaccessible cliffs, especially in coastal areas, are difficult to study in detail with only in situ techniques. This difficulty can be overcome by the complementary application of remote sensing methods. This work focuses on an active complex landslide affecting the slope of the Tazones Lighthouse (Cantabrian coast, North Iberian Peninsula), which has been monitored since June 2018. The aim of this research is to establish a conceptual model of the internal structure of the slope. A remote multitechnique approach was applied, including landscape deformation analysis from photogrammetric surveys, ground motion detection applying A-DInSAR techniques and Sentinel-1 satellite data, and electrical resistivity tomography. The obtained results showed the great potential of some of the remote techniques, such as UAV photogrammetry and electrical tomography, and the ineffectiveness of others, such as A-DInSAR, which failed to provide adequate results due to the profuse vegetation. This work made it possible to establish a geological model of the functioning of the slope of the Tazones Lighthouse and to deduce the surface extent of the destabilized mass (70,750 m2), the rupture surface shape (stepped), its in-depth extent (10–50 m), the volume of materials involved (~3,550,000 m3) and the type of landslide (complex including a predominant translational slide). The combination of field and remote sensing data significantly increased the possibility of reaching a comprehensive geological interpretation of landslides on rocky coasts.